Relationship between hamstring strength and hop performance at 8 and 12 months after ACL reconstruction with hamstring tendon autografts - Johan Högberg; Jakob Lindskog; Axel Sundberg; Ramana Piussi; Rebecca Simonsson; Kristian Samuelsson; Roland Thomeé; Eric Hamrin Senorski (BMC, 2024)
Abstract Background The relationship between hamstring strength and hop performance after anterior cruciate ligament (ACL) reconstruction with hamstring tendon (HT) autografts has not been well elucidated. The aim was to investigate the relationship between eccentric hamstring strength, assessed with the NordBord, and concentric hamstring strength, assessed with the Biodex, with hop performance at 8 and 12 months after ACL reconstruction. Methods Registry study. Patients ≥ 16 years who had undergone primary ACL reconstruction with HT autograft, followed by muscle strength and hop tests at 8 and 12 months were included. Correlations of the relative hamstring strength (Nm/kg or N/kg) and limb symmetry index (LSI) with hop performance were analyzed. Pearson's correlation coefficient, and coefficient of determination (r2) were used for statistical analysis. Results A total of 90 patients were included, of which 48 (53%) were women. The mean age at ACL reconstruction was 27.0 ± 8.0 years. Relative hamstring strength had significant positive correlations with hop performance, ranging from r = 0.25-0.66, whereas hamstring strength LSI had significant positive correlations which ranged from r = 0.22-0.37 at 8 and 12 months after ACL reconstruction. At 12 months, the relative hamstring strength in the Biodex explained 32.5-43.6% of the hop performance in vertical hop height, hop for distance relative to height, and the total number of side hops, whereas the relative hamstring strength in the NordBord explained 15.2-23.0% of the hop performance. Conclusion The relative hamstring strength in the Biodex test explained 32.5-43.6% of the hop performance, whereas the relative hamstring strength in the NordBord explained 15.2-23.0%. Thus, our findings suggest that relative hamstring strength, especially in the hip-flexed position may be a better indicator of hop performance at 8 and 12 months after ACL reconstruction in patients treated with HT autograft.